Rocking the Boat: The Decisive Roles of Rho Kinases During Oocyte, Blastocyst, and Stem Cell Development - Saadeldin, Islam M.; Tukur, Hammed A.; Aljumaah, Riyadh S.; Sindi, Ramya A. (Frontiers in Cell and Developmental Biology, 2021)
The rho-associated coiled-coil-containing proteins (ROCKs or rho kinase) are effectors of the small rho-GTPase rhoA, which acts as a signaling molecule to regulate a variety of cellular processes, including cell proliferation, adhesion, polarity, cytokinesis, and survival. Owing to the multifunctionality of these kinases, an increasing number of studies focus on understanding the pleiotropic effects of the ROCK signaling pathway in the coordination and control of growth (proliferation, initiation, and progression), development (morphology and differentiation), and survival in many cell types. There is growing evidence that ROCKs actively phosphorylate several actin-binding proteins and intermediate filament proteins during oocyte cytokinesis, the preimplantation embryos as well as the stem cell development and differentiation. In this review, we focus on the participation of ROCK proteins in oocyte maturation, blastocyst formation, and stem cell development with a special focus on the selective targeting of ROCK isoforms, ROCK1, and ROCK2. The selective switching of cell fate through ROCK inhibition would provide a novel paradigm for in vitro oocyte maturation, experimental embryology, and clinical applications.